Design of composite laminates for optimum frequency response - Kayıkçı, Rengin. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
In this study, natural frequency response of symmetric laminated composite plates was optimized. An analytical model accounting for bending-twisting effects was used to determine the laminate natural frequency. In this way, no limitations needed to be imposed on the stacking sequence of laminates to avoid error as in some of the previous studies. Two types of problem, fundamental frequency maximization and frequency separation maximization, were considered. Because of the existence of numerous local optimums, a global search algorithm, direct simulated annealing, was utilized as to find the optimal designs. Results were obtained for different plate aspect ratios. Effects of the number of design variables and the range of values they take on the optimal frequency were also investigated.
Keywords: Laminated materials.; Composite materials.; Plates (Engineering)